2011
DOI: 10.1631/jzus.b1000348
|View full text |Cite
|
Sign up to set email alerts
|

Association between moderately oxidized low-density lipoprotein and high-density lipoprotein particle subclass distribution in hemodialyzed and post-renal transplant patients

Abstract: Abstract:Disturbances in the metabolism of lipoprotein profiles and oxidative stress in hemodialyzed (HD) and post-renal transplant (Tx) patients are proatherogenic, but elevated concentrations of plasma high-density lipoprotein (HDL) reduce the risk of cardiovascular disease. We investigated the concentrations of lipid, lipoprotein, HDL particle, oxidized low-density lipoprotein (ox-LDL) and anti-ox-LDL, and paraoxonase-1 (PON-1) activity in HD (n=33) and Tx (n=71) patients who were non-smokers without active… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
23
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 20 publications
(32 reference statements)
3
23
0
1
Order By: Relevance
“…Rather it increased, but not significantly. However, our results are in agreement with a recent study by Kimak et al 21 who also showed a moderate increase in oxLDL and changes in other lipid parameters in transplant patients. Besides modulation of lipid parameters, a decrease in paraoxonase 1 (POX1) activity in CRF patients was observed.…”
Section: The Effect Of Immunosuppressivessupporting
confidence: 94%
See 1 more Smart Citation
“…Rather it increased, but not significantly. However, our results are in agreement with a recent study by Kimak et al 21 who also showed a moderate increase in oxLDL and changes in other lipid parameters in transplant patients. Besides modulation of lipid parameters, a decrease in paraoxonase 1 (POX1) activity in CRF patients was observed.…”
Section: The Effect Of Immunosuppressivessupporting
confidence: 94%
“…The mild increase in oxLDL after KT could be associated with incomplete restoration of POX1 activity and HDL function. 21,22 Our results also demonstrated that the level of AOPPs, one of the end products of OS, is a reliable and sensitive marker for estimating the effectiveness of therapy and the degree of OS in patients suffering from chronic kidney disease. Its determination seems to be better than oxLDL levels for monitoring the real situation in the body.…”
Section: The Effect Of Immunosuppressivessupporting
confidence: 58%
“…13 Kidney transplant recipients have hypertriglyceridemia; hypercholesterolemia; moderately decreased HDL cholesterol, HDL particle concentration, and PON1 activity; and moderately increased oxidized LDL and antioxidized LDL antibody levels compared with controls; however, oxidized LDL and antioxidized LDL antibody levels may be increased and PON1 activity may be decreased in hemodialysis patients. 14 These results show that oxidized LDL and decreased PON1 activity in transplant recipients may cause more mildly oxidized HDL, which may be less stable and which may undergo metabolic remodeling, generate a greater number of smaller pre-β-HDL particles, and accelerate reverse cholesterol transport. This may be beneficial for transplant recipients.…”
Section: Discussionmentioning
confidence: 76%
“…This may be beneficial for transplant recipients. 14 Another study concluded that immunosuppressive drug combinations do not affect PON activity. 15 After a kidney transplant, continuous immunosuppressive therapy (cyclosporine, azathioprine, and methylprednisolone) produced other predisposing factors for accelerating atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation